1986
DOI: 10.1093/jac/17.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Activity of ciprofloxacin against resistant clinical isolates

Abstract: The in-vitro activity of ciprofloxacin, a new quinolone derivative, was determined by broth microdilution for 518 clinical isolates. The MICs for 90% of the organisms were 2 mg/l for Pseudomonas aeruginosa, 8 mg/l for P. maltophilia, 4 mg/l for other Pseudomonas spp., 1 mg/l for Acinetobacter anitratus, 0.03-0.5 mg/l for differing species of Enterobacteriaceae, 2 mg/l for Streptococcus faecalis, 0.25 mg/l for coagulase-negative Staphylococcus spp. and 2 mg/l for S. aureus. Furthermore, on a weight basis, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our data indicated that ciprofloxacin and the quinolones from Abbott Laboratories (difloxacin and A-56620) were also only moderately active. These results were similar to those of Kelley et al (14) and several others (4-6, 13), even though different methods of susceptibility testing were used by these authors. It has been reported by several investigators that the cation concentration and type of medium used for susceptibility testing may greatly influence the in vitro activity of 3-lactams, aminoglycosides, and quinolones (1, 2, 9, 11, 17).…”
supporting
confidence: 92%
“…Our data indicated that ciprofloxacin and the quinolones from Abbott Laboratories (difloxacin and A-56620) were also only moderately active. These results were similar to those of Kelley et al (14) and several others (4-6, 13), even though different methods of susceptibility testing were used by these authors. It has been reported by several investigators that the cation concentration and type of medium used for susceptibility testing may greatly influence the in vitro activity of 3-lactams, aminoglycosides, and quinolones (1, 2, 9, 11, 17).…”
supporting
confidence: 92%
“…Of the 21 patients with negative cultures at the end of therapy, 11 were evaluated with follow-up cultures 21 to 30 days after the completion of therapy. Bacteriologic relapses occurred in 7 of the 11 patients (64%) but were not accompanied by clinical deterioration.…”
mentioning
confidence: 92%
“…The 4-quinolone ciprofloxacin appeared to be a promising agent in the treatment of staphylococcal infections because of its activity against methicillin-resistant strains (9,11,16). However, reports of emerging resistance of the staphylococci to ciprofloxacin are increasing (4,7,(13)(14)(15).…”
mentioning
confidence: 99%